1999
DOI: 10.1038/15623
|View full text |Cite
|
Sign up to set email alerts
|

A Rad3–Rad26 complex responds to DNA damage independently of other checkpoint proteins

Abstract: The conserved PIK-related kinase Rad3 is required for all DNA-integrity-checkpoint responses in fission yeast. Here we report a stable association between Rad3 and Rad26 in soluble protein extracts. Rad26 shows Rad3-dependent phosphorylation after DNA damage. Unlike phosphorylation of Hus1, Crb2/Rhp9, Cds1 and Chk1, phosphorylation of Rad26 does not require other known checkpoint proteins. Rad26 phosphorylation is the first biochemical marker of Rad3 function, indicating that Rad3-related checkpoint kinases ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
176
1
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 180 publications
(187 citation statements)
references
References 34 publications
7
176
1
1
Order By: Relevance
“…A small amount of Rad26 phosphorylation is also detectable in the absence of DNA damage at 32°C. This is consistent with earlier data that demonstrated that Rad26 is phosphorylated in several Rad checkpoint-deficient backgrounds (Edwards et al, 1999). Checkpoint-dependent phosphorylation of Hus1 has also been reported after several hours' exposure to HU.…”
Section: Rad4 Lies Upstream Of Cds1 In the Dna Replication Checkpointsupporting
confidence: 82%
See 3 more Smart Citations
“…A small amount of Rad26 phosphorylation is also detectable in the absence of DNA damage at 32°C. This is consistent with earlier data that demonstrated that Rad26 is phosphorylated in several Rad checkpoint-deficient backgrounds (Edwards et al, 1999). Checkpoint-dependent phosphorylation of Hus1 has also been reported after several hours' exposure to HU.…”
Section: Rad4 Lies Upstream Of Cds1 In the Dna Replication Checkpointsupporting
confidence: 82%
“…Activation and phosphorylation of Cds1 is S-phasespecific in response to either inhibition of DNA replication or DNA damage, and kinase activation correlates with phosphorylation of the protein , providing a useful marker for the S-M checkpoint. Rad9 and Rad26 are also phosphorylated in response to radiationinduced DNA damage and Hus1 is phosphorylated in response to both DNA damage and prolonged inhibition of DNA replication (Kostrub et al, 1998;Edwards et al, 1999;Caspari et al, 2000a;Caspari et al, 2000b). Ultimately, all of these phosphorylation events have been demonstrated to be Rad3-dependent and this has enabled hierarchical relationships between fission yeast checkpoint proteins to be determined.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…ATR signalling is also induced by bulky DNA adducts, lesions resulting from ultraviolet radiation (UV), such as pyrimidine dimers and the 6-(1,2)-dihydro-2-oxo-4-pyrimidinyl-5-methyl-2,4-(1H,3H)-pyrimidinediones (Unsal-kacmaz et al, 2002). In humans, ATR is stably associated with ATRIP (ATR/ATRIP), this is also the case in yeast (Mec1/Dcd2 in S.cerevisiae (budding yeast) and Rad3/Rad56 in Schizosaccharomyces Pombe (S.pombe, fission yeast) (Cortez et al, 2001;Unsal-kacmaz and Sancar, 2004;Paciotti et al, 2000;Edwards et al, 1999). ATR is thought to be constitutively active during unstressed DNA replication, thus it is believed that during S phase substrate reactions are reliant on cellular localisation (Niida and Nakanishi, 2006).…”
Section: Atr Activation In Response To Single Strand Dna Damagementioning
confidence: 98%